2023
DOI: 10.3389/fpubh.2023.1129004
|View full text |Cite
|
Sign up to set email alerts
|

Health behavior of Austrian tertiary students focusing on diet type linked to sports and exercise—first glimpse of results from the “sustainably healthy—from science 2 high school and university” study

Abstract: BackgroundThere is a strong association between lifestyle behavior and health status. While young adulthood is a critical period for adopting and stabilizing lifelong healthy behavior, university life is independently associated with psychological stressors that may further affect health and well-being.ObjectiveThe present multidisciplinary study aimed to examine the health behavior of Austrian college and university students, differentiated based on diet types (vegan, vegetarian, and omnivorous) and physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
2
2
0
Order By: Relevance
“…This finding is partially in line with other national and international reports (including the Global Nutrition Report-Austria), indicating a higher prevalence of overweight/obesity among male adults compared to females [48][49][50][51]. Similar results were also reported from a series of Austrian studies conducted on school pupils and teachers [52,53] and university students and staff [54,55], as well as two Brazilian investigations on bank employees [56,57]. However, a study conducted on Ghanaian bank employees shows that, although highly prevalent in general (55.6%), there was no significant gender difference in the prevalence of overweight/obesity [58].…”
Section: Anthropometrysupporting
confidence: 90%
“…This finding is partially in line with other national and international reports (including the Global Nutrition Report-Austria), indicating a higher prevalence of overweight/obesity among male adults compared to females [48][49][50][51]. Similar results were also reported from a series of Austrian studies conducted on school pupils and teachers [52,53] and university students and staff [54,55], as well as two Brazilian investigations on bank employees [56,57]. However, a study conducted on Ghanaian bank employees shows that, although highly prevalent in general (55.6%), there was no significant gender difference in the prevalence of overweight/obesity [58].…”
Section: Anthropometrysupporting
confidence: 90%
“…Consistent with the present findings, data from a 2019 national report showed that there is a gradual increase in the prevalence of overweight and obesity across four age categories in adulthood, starting from 29.4% (among people aged 15-30 years) to 65.8% (among those aged 60-75 years) [80]. Comparable findings were also documented in Austrian investigations carried out among school teachers [88], university students [89], and university professors [90]. The age-associated difference in the prevalence of excess body weight could potentially be attributed to a combination of various factors, including a decreased metabolic rate, evolving lifestyles, and dietary habits [91].…”
Section: Anthropometrysupporting
confidence: 90%
“…While the distribution of sex and age within the present study groups was normal and insignificant, other factors such as dietary habits, stress levels, and workplace culture may play a key role in explaining the above difference. Consistently, data from large-scale Austrian studies spanning various age groups demonstrate that PA patterns are linked to the interplay of several lifestyle factors [65][66][67][68], highlighting the significance of recognizing diverse health determinants.…”
Section: Discussionmentioning
confidence: 62%